Plink /Amir Harith Azri and Muhammad Alif Ilman Mohd Nazri - Azri, Amir Harith; Mohd Nazri, Muhammad Alif Ilman (2020)
Ever since the plastics industry began in 1900s, the production of plastics has shown a dramatic increase globally as the world is moving towards year 2050. Ironically, most plastics are only being used once and discarded to the landfills and oceans. This phenomenon will be one of the most crucial problem of the century. Hence, a lot of research has been done to study the potential usage of plastic waste in various field. Thus, this study was aimed to find an alternative way to recycle plastics waste into a beneficial product without polluting the environment. PLINK enables those plastic waste to become a useful plastic ink in the form of crayon and can be used widely in the arts and batik making field. Py.rolysis method has been used to extract crude oil from the plastic waste will then undergo petroleum distillation to get petrol that is then change into wax by deoiling. Then organic color pigment is aded to the wax to create a crayon mixture in order to obtain PLINK. PLINK has been tested by the students from the Faculty of Arts and Design at UITM Shah Alam in their art painting classes. Results showed that PLINK has been one of the most green and compatible with the commercial crayons in the market. The simple techniques that need to be apply in using PLINK especially as batik mixture and dyes for shirts was accredited to be green and eco-friendly for the users. PLINK has been proven to be one of the best ways to make abundance of plastic waste more useful and provide a greener way of using crayon in arts and batik making field.